GESTION INTÉGRÉE DES RESSOURCES EN EAU DANS LE TAFILALET (SUD-EST MAROCAIN) ; LEÇONS D’UNE HISTOIRE - Ben Brahim, Mohammed (Riparia, 2016)
In the eighth century, the Arab settlement in the pre-Saharan south-eastern Morocco led to the conceptualization of the Tafilelt’s spatial configuration; which reveals some concerns with regards to the exploitation of natural resources, land use, planning of economic development linked to water as well as environmental risk management. The number of research conducted during the last decades, concerning the interactions between the society and the environment in the oases of the pre-Saharan south-eastern Morocco, helped improving the comparative history of the environment. This is in the sense that they revealed some unpublished indicators influencing the medieval Muslim Arab heritage on water resources management practices adapted to the future. The relationship between the Tafilelt population and water represents an important aspect of the oasis heritage. In fact, incorporating traditional management knowledge and skills into modern society is something playing in favor of the region’s success.